Single-cell deconvolution algorithms analysis unveils autocrine IL11-mediated resistance to docetaxel in prostate cancer via activation of the JAK1/STAT4 pathway - Bisheng Cheng; Lingfeng Li; Tianlong Luo; Qiong Wang; Yong Luo; Shoumin Bai; Kaiwen Li; Yiming Lai; Hai Huang (Journal of Experimental & Clinical Cancer Research, 2024)
Abstract Background Docetaxel resistance represents a significant obstacle in the treatment of prostate cancer. The intricate interplay between cytokine signalling pathways and transcriptional control mechanisms in cancer cells contributes to chemotherapeutic resistance, yet the underlying molecular determinants remain only partially understood. This study elucidated a novel resistance mechanism mediated by the autocrine interaction of interleukin-11 (IL-11) and its receptor interleukin-11 receptor subunit alpha(IL-11RA), culminating in activation of the JAK1/STAT4 signalling axis and subsequent transcriptional upregulation of the oncogene c-MYC. Methods Single-cell secretion profiling of prostate cancer organoid was analyzed to determine cytokine production profiles associated with docetaxel resistance.Analysis of the expression pattern of downstream receptor IL-11RA and enrichment of signal pathway to clarify the potential autocrine mechanism of IL-11.Next, chromatin immunoprecipitation coupled with high-throughput sequencing (ChIP-seq) was performed to detect the nuclear localization and DNA-binding patterns of phosphorylated STAT4 (pSTAT4). Coimmunoprecipitation and reporter assays were utilized to assess interaction between pSTAT4 and the cotranscription factor CREB-binding protein (CBP) as well as their role in c-MYC transcriptional activity. Results Autocrine secretion of IL-11 was markedly increased in docetaxel-resistant prostate cancer cells. IL-11 stimulation resulted in robust activation of JAK1/STAT4 signalling. Upon activation, pSTAT4 translocated to the nucleus and associated with CBP at the c-MYC promoter region, amplifying its transcriptional activity. Inhibition of the IL-11/IL-11RA interaction or disruption of the JAK1/STAT4 pathway significantly reduced pSTAT4 nuclear entry and its binding to CBP, leading to downregulation of c-MYC expression and restoration of docetaxel sensitivity. Conclusion Our findings identify an autocrine loop of IL-11/IL-11RA that confers docetaxel resistance through the JAK1/STAT4 pathway. The pSTAT4-CBP interaction serves as a critical enhancer of c-MYC transcriptional activity in prostate cancer cells. Targeting this signalling axis presents a potential therapeutic strategy to overcome docetaxel resistance in advanced prostate cancer. Graphical Abstract